Pengaruh Dukungan Sosial terhadap Motivasi Belajar Mahasiswa Tingkat Ii - Dinda Dewi Santri; Defi Astriani (Syntax Corporation Indonesia, 2024)
This study examines the relationship between work motivation and psychological well-being (PWB) in internship students in Greater Jakarta. Program policies provide opportunities for students to develop their skills and work experience. This study aims to identify how work motivation, both intrinsic and extrinsic, affects the psychological well-being of internship students. Using a predictive correlational approach, data was collected through a questionnaire that measured the dimensions of work motivation and PWB. The results of the study showed that intrinsic motivation had a significant positive impact on psychological well-being, while excessive extrinsic motivation could have a negative impact. This research emphasizes the importance of creating a supportive work environment to motivate interns, improve their performance, and prepare them for the transition from academia to the world of work. The researcher obtained 103 respondents from various students at the University of Greater Jakarta with 25.2% male and 74.8% female. The data of this study was processed using convenience sampling techniques, using Multidimensional Work Motivation Scale (MWMS) and Psychological Well-Being (PWB) questionnaires. The results of data analysis are known through the Kolmogorov Smirnov test obtained a number of 0.200 > 0.05 for both variables, it was concluded that the residual data was normally distributed.